Organisational Improvisation as a Metaphor of Jazz Improvisations in Contemporary Art Organisations - Masaitytė, Daiva; Jurėnienė, Virginija (Vilnius University Open Series, 2022)
The article discusses the concept of organisational improvisation and reveals why it is important for contemporary organisations. Organisational improvisation is more and more acknowledged as a relevant field of management research; however, heads of most organisations still believe that detailed plans accompanied by various bureaucratic procedures are important, and that improvisation is a sign of failure, is risky and is to be avoided. The article discusses the three levels of improvisation (individual, interpersonal and organisational) pointing out its possibilities and advantages. Peculiarities of organisational improvisation are provided along with the results of a case study of public institution Jazz Academy. In this way, this article is the first study of organisational improvisation in Lithuania. The aim of the article is to reveal the peculiarities of organisational improvisation.